Layer selective determination of magnetization vector configurations in an epitaxial double spin valve structure: Si(001)/Cu/Co/Cu/FeNi/Cu/Co/Cu - Choi, B; Samad, A; Vaz, C; Bland, J; Langridge, S; Penfold, J (2000)
The magnetization vector configurations in an epitaxial Si(001)/Cu/Co/Cu/Fe 20Ni 80/Cu/Co/Cu double spin valve structure have been investigated at room temperature using polarized neutron reflectivity measurements. The layer-averaged magnetic moment per FeNi atom was found to be 0.99±0.06 μ B at saturation, while the top (bottom) Co layer moment was 1.69±0.09 μ B (1.67 ±0.08 μ B), which are identical to the bulk values within experimental error. Furthermore, the Co magnetization vectors are found to lie in-plane but canted with respect to the applied field direction for an applied field strength smaller than the coercive fields (∼80 and 130 Oe) of the Co layers. This result indicates that a complete antiparallel alignment of the layer magnetizations is not reached causing a corresponding reduction in the giant magnetoresistance (GMR). These observations emphasize the importance of the delailed spin configuration in determining the GMR amplitude at low fields. © 2000 American Institute of Physics.